DEVELOPMENT TRENDS OF THE MINING INDUSTRY OF UKRAINE IN THE GLOBAL CONTEXT - MYKHAILOV, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main global trends in the development of the mining industry in recent years are considered; a constant increase in the intensity of development of the earth’s subsoil and extraction of mineral products in recent decades is shown; the world’s largest mining countries are highlighted. It was established that China (23 % of world production), the USA (12 %), Russia (9 %), and Australia (7 %) are the leading countries in terms of production volume. China, the USA, Russia, Saudi Arabia and Australia are the leaders in terms of the value of mined products. It has been established that in recent years (2015–2021) the growth of mining of lithium, rare earths, niobium, titanium, bauxite, nickel, fluorite, graphite, etc. was especially rapid, while the mining of tin, mercury, antimony, uranium, tantalum, technical diamonds, etc. decreased. It was established that at the end of the 20s, the development of the mining industry was negatively affected by the consequences of the pandemic, but already at the end of 2020, the state of the mining industry began to improve. The role and place of Ukraine in the global mining industry is shown, which ranks 24th in the world in terms of volume of production, and 36th in terms of the value of mined products; and takes leading positions in the production of iron, manganese, titanium, etc. In recent years (2015–2021), the production of iron, manganese, titanium, feldspar, graphite, sulfur, and coking coal has increased significantly in Ukraine, but the production of gallium, bentonite, salt, zircon, coal, and uranium has decreased.